HADITS-HADITS TENTANG KEADILAN GENDER - Ali Mohtarom (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2021)
In general, the difference between men and women in terms of sex / gender is biologically termed natural differences which are absolutely non-exchangeable. Women have a uterus, breasts, ovaries, menstruation, get pregnant and give birth. Meanwhile, men have a penis and sperm for fertilization. This difference is natural throughout the ages and applies to all humans everywhere, regardless of the rich, poor, officials or people, urban or rural. The differences between men and women that result from social andsymbolic interpretations or social construction, or non-natural differences, can change from time to time or place.This research uses descriptive qualitative research methods. Research aimed at describing and analyzing phenomena, events, social activities, attitudes, beliefs, perceptions, and thoughts of people individually or in groups The. traditions about gender in this discussion are arranged based on these classifications and / or thematically, namely the problem of creating women. , regarding the duties / responsibilities of husband and wife, regarding the priorities of men, regarding women's leadership, as well as those related to the partnership of men and women.